A review of CO2 sorbents for promoting hydrogen production in the sorption-enhanced steam reforming process. (1st July 2021) - Wang, Yinxiang; Memon, Muhammad Zaki; Seelro, Majid Ali; Fu, Weng; Gao, Yuan; Dong, Yingchao; Ji, Guozhao
Abstract: Sorption-enhanced-steam-reforming (SESR) is a thermochemical conversion technology that produces a high-purity hydrogen stream by utilizing in-situ removal of CO2 with a sorbent. In this paper, the advantages and disadvantages of CaO based sorbents, alkali-metal based sorbents (Na2 ZrO3, Li2 ZrO3 and Li4 SiO4 ), hydrotalcite based sorbents, bifunctional materials and sorbents prepared from wastes are briefly discussed, and the techniques to improve the sorption properties of these CO2 sorbents are summarized. In the process of hydrogen production by sorption-enhanced-steam-reforming, the selection of suitable high-temperature CO2 sorbent is the key to produce high purity hydrogen. Furthermore, the hydrogen-production performance of the above-mentioned sorbents in the SESR process is investigated and summarized. Finally, a future perspective and some suggestions regarding these five types of sorbents are put forward. Highlights: Ca-sorbents are suitable to enhance H2 in high temperature reforming at 550–800 °C. Alkali metal ceramics are generally used for H2 yield between 550 and 600 °C. The application of HTlc is limited to reforming reactions below 500 °C. Bi-functional materials are used in SESR due of reduced mass transfer resistance. Using waste to prepare CO2 sorbents is a promising direction for future research.